Million dollar consulting : the professional's guide to growing a practice - Weiss, Alan (New York : McGraw-Hill, 2003)
Offers advice on turning a consulting business into one which generates $1,000,000 or more annually through landing powerful clients, integrating new technology, and improving a firm's image.
Includes bibliographical references (p. 341-350) and index.
enc
Ref.
Keywords: Consultants -- Marketing; Business consultants--Marketing; Consultants; Marketing; United States